Atherogenic Indices in Type 2 Diabetic Iraqi Patients and Its Association with Cardiovascular Disease Risk - Ahmed, Hind Sh.; Mohammed , Melak S. (Journal of the Faculty of Medicine Baghdad, 2023)
Background: Diabetes is a serious risk factor for atherosclerotic cardiovascular disease and an important cause of mortality. Dyslipidemia is commonly related to type 2 diabetes and the atherogenic index of plasma is a strong marker to predict the risk of atherosclerosis and coronary heart disease.Objective: To study the association of atherogenic indices lipids in type 2 diabetic Iraqi patients with cardiovascular disease.Methods: This clinical study was conducted at Baghdad Teaching Hospital/ Medical City-Baghdad from October 2022 to February 2023. Sixty type 2 diabetic patients were recruited for this study; 30 patients with cardiovascular disease and 30 without cardiovascular disease. Their ages were between 40-55 years. Another 30 healthy individuals were selected as a control group.Results: There were considerable rises in glycemic and lipid investigations in diabetic patients with cardiovascular disease compared to those without cardiovascular disease and the control group. The present results show higher levels of lipid ratios in diabetic patients with cardiovascular disease. The results also revealed high levels of non-high-density lipoprotein cholesterol for diabetic patients with cardiovascular disease (241.8±12.24 mg/dL) versus (150.1±7.12 and 68.9±5.1 mg/dL) for those without cardiovascular disease and the controls group respectively. The atherogenic index of plasma in diabetic patients with cardiovascular disease as compared to diabetic and healthy control groups were (0.8±0.09) versus (0.7±0.03 and 0.2±0.08) respectively. There was a significant correlation between the atherogenic index of plasma and anthropometric factors, glycemic and lipid profile with their ratios in diabetic patients with and without cardiovascular disease. Conclusions: The results of this study confirm that the lipid indices are risk indicators of glycemic control with higher prognostic value than traditional factors. So, non-high-density lipoprotein cholesterol and atherogenic index of plasma can be used as a significant predictor of glycemic control